2019
DOI: 10.1001/jamaoto.2019.2302
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomic Distribution of the Morphologic Variation of the Upper Lip Frenulum Among Healthy Newborns

Abstract: IMPORTANCE The maxillary labial frenulum and its potential contribution to breastfeeding difficulty may substantially affect public health. However, objective studies of the frenulum are limited. OBJECTIVE To measure the variations in length, thickness, and attachments of the maxillary labial frenulum in healthy newborns and to identify which anatomic measurements could be used in further research investigating the maxillary labial frenulum. DESIGN, SETTING, AND PARTICIPANTS This prospective cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Anatomical studies such as our own have failed to show a link between appearance of the maxillary frenulum and breastfeeding ability 18 . Other variables, such as length, flexibility, extensibility, and lip attachment site of the maxillary frenulum may therefore be more important in evaluating the impact of the frenulum on breastfeeding 7,19 . This is similar to the growing body of evidence on tongue tie, showing that anatomy alone is insufficient to determine impact on breastfeeding, and that the function of important oral structures (tongue, lips) must also be considered.…”
Section: Discussionsupporting
confidence: 56%
“…Anatomical studies such as our own have failed to show a link between appearance of the maxillary frenulum and breastfeeding ability 18 . Other variables, such as length, flexibility, extensibility, and lip attachment site of the maxillary frenulum may therefore be more important in evaluating the impact of the frenulum on breastfeeding 7,19 . This is similar to the growing body of evidence on tongue tie, showing that anatomy alone is insufficient to determine impact on breastfeeding, and that the function of important oral structures (tongue, lips) must also be considered.…”
Section: Discussionsupporting
confidence: 56%
“…Later on it recedes and takes more apical position. 19,23 If the continuous band of maxillary labial frenum crosses in between the two maxillary central incisors, it causes midline diastema and is also reported to affect the growth of premaxillary region. 1,24,25 In this instance, the papillary and papillary penetrating frenum attachment are the only two considered as pathological.…”
Section: Discussionmentioning
confidence: 99%
“…The author's concluded that the"… classification system proposed by Kotlow has not been found reliable both in terms of inter and intraobserver agreement and in terms of predicting the severity of the breastfeeding difficulties." Another exciting new publication suggests that a more meaningful assessment of the magnitude of frenulum tethering would necessitate a compilation of parameters including distance from alveolar ridge, width of attachment, length of free lip, and flexibility of frenulum, not the location of frenulum insertion alone [ 35 ]. It is of further interest to note that, in a study by Dollberg et al [ 28 ], follow-up interviews 2 weeks following birth found no association between the most severe cases of "tongue" or "lip-tie" with mothers who choose to cease breastfeeding due to difficulties.…”
Section: Discussionmentioning
confidence: 99%